“Amazônia é o mundo”: infância e criação poética na Reserva Extrativista Verde Para Sempre - Vieira, Paulo Roberto; Darwich, Rosangela Araujo; Guerra, Gutemberg Armando Diniz (Revista Brasileira de Educação Ambiental (RevBEA), 2025)
This article aims to investigate the impact of awareness-raising and inclusive activities that integrate poetry and local cultural elements into the creative expression of native children from the Amazon rainforest. The research was conducted through the workshop “Children, Forests, and Poetry,” held in the Arimum community, within the Verde para Sempre Extractive Reserve (RESEX) in Porto de Moz (PA), with 25 participants aged 5 to 12. Grounded in Paulo Freire’s pedagogy, the workshop connected everyday elements to oral and written expression. Future studies may investigate how these practices influence, in the long term, children’s environmental and cultural engagement, as well as their adaptation to different Amazonian contexts.